2018
DOI: 10.1513/annalsats.201708-687oc
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and Adverse Outcomes in a Chronic Obstructive Pulmonary Disease Population with a High Burden of Comorbidities. An Analysis from SPIROMICS

Abstract: Rationale: Chronic obstructive pulmonary disease (COPD) is a common cause of morbidity and associated with a significant burden of comorbidities. Although anemia is associated with adverse outcomes in COPD, its contribution to outcomes in individuals with other comorbid chronic diseases is not well understood. Objectives: This study examines the association of anemia with outcomes in a large, well-characterized COPD cohort, and attempts to understand the contribution of anemia to outcomes and phenotypes in ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 34 publications
3
26
0
Order By: Relevance
“…Consistent with the physiological relevance of anaemia, several clinical studies in COPD have reported a significant deleterious effect of anaemia on exercise capacity, with anaemic patients being more dyspnoeic and exhibiting functional exercise limitation12 14 36 and reduced maximal O 2 consumption 12. In a regression analysis, higher Hb levels were independently associated with improved exercise capacity and HRQoL 37.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Consistent with the physiological relevance of anaemia, several clinical studies in COPD have reported a significant deleterious effect of anaemia on exercise capacity, with anaemic patients being more dyspnoeic and exhibiting functional exercise limitation12 14 36 and reduced maximal O 2 consumption 12. In a regression analysis, higher Hb levels were independently associated with improved exercise capacity and HRQoL 37.…”
Section: Introductionmentioning
confidence: 70%
“…Inflammatory cytokines such as interleukin (IL)-1, IL-6, IL-10, IL-22, interferon-γ and tumour necrosis factor 1-α interfere with the normal function of several molecules involved in iron metabolism 41 42. These inflammatory markers are generally increased in anaemic patients with chronic lung disease and are associated with reduced serum iron levels and decreased iron availability for erythropoiesis;36 43 they are believed to do this through the destruction of red blood cell precursors and decreasing the number of EPO receptors on progenitor cells 44. Interestingly, this increase in inflammatory cytokines, particularly IL-6, is also considered to be an innate immune response to infection as it reduces iron availability for the growth of extracellular pathogens and is relevant to respiratory populations predisposed to bacterial and viral infections 42.…”
Section: Introductionmentioning
confidence: 99%
“…bIOMArKErs Complete blood counts are frequently obtained in clinical practice and are readily available for many patients. Both normocytic anaemia and thrombocytosis were found to be independently associated with worse dyspnoea and respiratory-related quality of life in individuals with COPD 32,33 . In addition, thrombocytosis was linked to a higher likelihood of all COPD exacerbations (adjusted OR 1.5; 95% CI 1.1-2.0) and severe COPD exacerbations (adjusted OR 1.5; 95% CI 1.1-2.2) during the preceding year in a combined analysis of the SPIROMICS and COPDGene cohorts 33 .…”
Section: Chest Imagingmentioning
confidence: 94%
“…Furthermore, total levels of non-heme iron and of other iron-binding molecules including lipocalin-2 and lactoferrin, are increased in lung tissue, sputum, BALF, and AMs of COPD patients, relative to non-smokers 9,[11][12][13][14][15][16][17][18][19][20][21] . Conversely, there is also ample evidence for iron deficiency in COPD, and anaemia in COPD is associated with worse patient outcomes, including mortality 22,23 . The biological relevance of such observations remains to be elucidated; however, these data strongly support a local iron overload signature in the extracellular milieu of the lung in COPD that is distinctive to systemic iron handling, which is intriguing as mainstream cigarette smoke contains little iron 24,25 .…”
mentioning
confidence: 99%